Motivasi Kebangkitan Dunia Islam Pada Abad XIX-XX - M Dahlan M (Jurnal Adabiyah: Humanities and Islamic Studies, 2015)
The purpose of this essay is to describe the motivation of the resurrection in Islamic World in the XIX – XX century. As is well known, after three great kingdoms in the Islamic world (Ottoman, Safavid and Mughal) suffered a setback, Countries in Europe appear to be a new power in the world in the XIX century. This situation caused Muslims become a minority and marginalized people in the world. However, the motivation to restore the glory of Islam still exists because of the strong impulse of the doctrine of Islam. So that gradually the Muslims were able to rise again, either by way of modernization or purification of Islam. It can be seen from the development of various Islamic countries with a majority of Muslims in it, such as Saudi Arabia, Turkey, India (before was split into Pakistan) and Indonesia.